Political participation and ethnic minorities : Chinese overseas in Malaysia, Indonesia, and the United States - Freedman, Amy L. (Routledge, 2000)
Annotation Amy Freedman's empirical study examines the hows and whys of Chinese overseas political activity in three diverse countries.
Keywords: Chinese -- Foreign countries -- Politics and government.; Chinese -- Southeast Asia.; Chinese -- United States.; Minorities -- Political activity.; Chinois -- Asie du Sud-Est.; Minorités -- Activité politique.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Chinese; Minorities -- Political activity; Southeast Asia; United States